Enhancing Digital Learning in Higher Education: The Mediating Role of Academic Self-Efficacy in Motivation and Engagement - Nurrahmah Agusnaya; Abdul Wahid; Muh. Akbar; Wahyu Hidayat M; Sanatang Sanatang; Soeharto Soeharto; Zsolt Lavicza (CV FOUNDAE, 2024)
This study investigates the impact of Relevant and Applicable Content (RAC) and Learner Support (LS) on Motivation and Engagement (ME) in digital learning, mediated by Academic Self-Efficacy (ASE). Higher education faces challenges in maintaining student motivation and engagement along with the rapid growth of digital learning technologies. However, limited research has explored the roles of RAC and LS in this context. This study aimed to address this gap by examining ASE's mediating influence. A quantitative approach was utilized, collecting data through self-report questionnaires from 375 university students. Structural Equation Modeling (SEM) was used to analyze the relationships among variables. The results revealed that RAC and LS positively influenced ME directly and indirectly through ASE. These findings emphasize the need for relevant content and robust learner support to design effective digital learning programs. Implementing these strategies can foster motivation, engagement, and student-centred learning outcomes in higher education